Components of coated vesicles and nuclear pore complexes share a common molecular architecture - Devos, Damien (PLoS biology, 2004)
Structural similarities between the proteins of a nuclear pore subcomplex and proteins comprising vesicle coating complexes indicate a common origin for nuclear pore complexes and coated vesicles.